Dampak Game Online Terhadap Keharmonisan Rumah Tangga - Hasibuan, Selli Mariyana; Sirait, Adi Syahputra (Jurnal El-Thawalib, 2022)
Family harmony is a condition where family members are full of calm, tranquility, love, mutual understanding, dialogue and good cooperation between family members. Family harmony can be seen with the responsibility in fostering a family based on mutual respect, mutual acceptance, respect, mutual trust and love for each other. A harmonious family is a family that can lead a person to live a happier, more worthy and more peaceful life. Family harmony is characterized by unified relationships, open communication and warmth among family members. A harmonious family is a condition where all members carry out their respective rights and obligations, there is love, mutual understanding, good communication and cooperation between family members. A harmonious family is a happy and positive place to live, because family members have learned several ways to treat each other well. Family members can support each other, give love and have an attitude of loyalty, communicate openly between family members, respect each other and enjoy togetherness. However in today’s era, and the development of technology such as cellphones and so on, where this cellphones is one of the causes of the destruction of domestic life that has been built for years, and many families who used to be harmonious families have become destroyed by one of the games on the cellphone, namely online games, which is where the online game became one of the triggers for the destruction of the family. Because these online games have been played by many people, not even fathers and mothers, there are also many who play online games so that they forget their responsibilities and obligations as the head of the household and so on. So that online games have a very bad effect on household harmony